Application of a hemophilia mortality framework to the Emicizumab Global Safety Database. (16th December 2020) - Peyvandi, Flora; Mahlangu, Johnny N.; Pipe, Steven W.; Hay, Charles R. M.; Pierce, Glenn F.; Kuebler, Peter; Kruse‐Jarres, Rebecca; Shima, Midori
Abstract: Background: As the first non‐factor replacement therapy for persons with congenital hemophilia A (PwcHA), emicizumab's safety profile is of particular interest to the community. Objectives: We applied an algorithm for categorization of fatal events contemporaneous to emicizumab using reporter‐assessed causality documented in the Roche Emicizumab Global Safety Database. Patients/Methods: All fatalities in PwcHA reported to the database (from clinical trials, pre‐market access, and spontaneous post‐marketing reports) were categorized into: associated with hemophilia A—hemorrhagic, thrombotic, human immunodeficiency virus (HIV)/hepatitis C virus (HCV), hepatic (non‐HCV); associated with general population—trauma/suicide, non‐HA‐associated conditions; or, unspecified. Reported cause of death was not reassessed. Results: As of cut‐off May 15, 2020, 31 fatalities in PwcHA taking emicizumab were reported. Median age at death was 58 years; 51% had factor VIII inhibitors. Fifteen fatalities were considered associated with HA; overall, the most frequent category was hemorrhage (11/31). Of these, six had a history of life‐threatening bleeds, and four had a history of intracranial hemorrhage. The remaining HA‐associated fatalities were related to HIV/HCV (3/31) and other hepatic causes (1/31). No cases were categorized as thrombotic. Of 10 cases considered not associated with HA, two were categorized as cardiovascular (non‐thrombotic), five as infection/sepsis, and one each of trauma/suicide, pulmonary, and malignancy. Six cases were unspecified. Conclusions: No unique risk of death was associated with emicizumab prophylaxis in PwcHA. The data reveal that mortality in PwcHA receiving emicizumab was primarily associated with hemorrhage or non‐HA‐associated conditions, and was not reported by treaters to be related to emicizumab treatment.